Experience with UV‐C Air Disinfection in Some Russian Hospitals. (28th March 2021) - Volchenkov, Grigory
Abstract: Although the environmental control measure of ultraviolet germicidal irradiation (UVGI) for disinfection has not been widely used in the United States and some parts of the world in the past few decades, this technology has been well applied in Russia. UVGI technology has been particularly useful with regard to limiting TB transmission in medical facilities. There is good evidence that UV‐C (180−280 nm) air disinfection can be a helpful intervention in reducing transmission of the SARS‐CoV‐2 virus. Abstract : Although the environmental control measure of ultraviolet germicidal irradiation (UVGI) for disinfection has not been widely used in the United States and some parts of the world in the past few decades, this technology has been well applied in Russia. UVGI technology has been particularly useful with regard to limiting TB transmission in medical facilities. There is good evidence that UV‐C (180−280 nm) air disinfection can be a helpful intervention in reducing transmission of the SARS‐CoV‐2 virus.